Hydrophobic mesoporous TiO2 / carbonaceous composite material and preparation method and application thereof
By using hydrophobic mesoporous TiO2/carbonaceous composite materials as catalysts, combined with the modification technology of aminosilane coupling agents, an acid-base synergistic catalytic system is formed, which solves the oxidation and corrosiveness of traditional catalysts, and achieves the efficient, stable and environmentally friendly catalytic effect of the esterification reaction.
Patent Information
- Application Number
- CN202211143192.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-09-20
AI Technical Summary
The catalysts used in the existing esterification reaction, such as concentrated sulfuric acid, have strong oxidation and corrosion problems, and traditional liquid homogeneous acid catalysts have shortcomings in terms of environmental friendliness and reusability.
The hydrophobic mesoporous TiO2/carbonaceous composite material is used as a catalyst, and the sulfonate-based carbonaceous material is supported by mesoporous TiO2, and modified with aminosilane coupling agent to form an acid-base synergistic catalytic system to improve catalytic activity and stability.
The efficient catalysis of the esterification reaction was achieved, with high product selectivity, a conversion rate of 100%, a mild reaction and high yield, and the catalyst still maintained a catalytic effect of 88.6% after multiple cycles.
Smart Images

Figure CN116037182B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanocomposite material catalysis, and particularly relates to a hydrophobic mesoporous TiO2 / carbonaceous composite material and a preparation method and application thereof. Background Art
[0002] With the gradual development of science and technology, mechanical processing, manufacturing and use have become more and more popular. The global demand for lubricants has been increasing year by year. In 2021, the domestic demand for lubricants is expected to reach 8.2 million tons, with a growth rate of 3%. It is also worth noting that with the popularization of green chemical concepts in various countries, high-quality environmentally friendly lubricants are gradually replacing traditional lubricants and receiving more attention.
[0003] Bio-based synthetic ester oil is considered to be one of the most valuable and promising lubricants in future lubrication engineering. Among them, polyol ester oil has good chemical stability, good environmental benefits, good lubricity and low cost (Khubaib SM, Luo Y. Experimental investigation on solubility and viscosity of 1,1,1,2,3,3,3-heptafluoropropane (R227ea) and polyol ester oil (POE 22) Mixtures. Journal of Chemical & Engineering Data. 2022, 67, 1, 104-112). In industry, its synthesis method is mostly direct esterification, which is simple to operate, fast and controllable in reaction rate, but the catalyst plays a very important role in this method. Most existing esterification reactions are catalyzed by acidic homogeneous or heterogeneous catalysts, which act as proton donors for carboxylic acids during the reaction. Inorganic acid catalysts such as concentrated sulfuric acid, due to their strong acidity, show good catalytic activity in esterification reactions. However, the strong oxidizing property of trimethylolpropane ester brings a series of problems such as strong corrosion and excessive side reactions. The production of trimethylolpropane ester requires a new environmentally friendly catalyst.
[0004] In contrast, compared with traditional liquid homogeneous acidic catalysts, solid heterogeneous catalysts that are "green" and reusable are more popular. This ideal heterogeneous catalyst should have multiple properties, such as sufficient acid centers, high stability and low cost. Using solid acid instead of traditional acid as a catalyst will transform the reaction from homogeneous to heterogeneous, making it easy to separate the product and catalyst. At the same time, it is less corrosive to the equipment and can be reused. It is a relatively promising catalyst (Chen JZ, Liu H, Chen LM, et al. Carbon nanotube-based solid sulfonic acids as catalysts for production of fatty acid methyl ester via transesteriflcation and esterification. ACS Sustainable Chemistry & Engineering, 2016, 4, 3140-3150). The solid acids currently used for acid-catalyzed reactions include metal oxides, molecular sieves, cation exchange resins and carbon-based solid acids. Among them, carbon-based solid acids are simple to prepare, low in cost, and highly stable. The research on their preparation and catalytic performance has become a hot topic of research and is widely used in reaction processes such as esterification and hydrolysis (Zhao Bo. Research Progress on Solid Acid Catalyzed Hydrolysis of Cellulose to Glucose [J]. Chemical Industry Progress, 2017.). However, the specific surface area of carbon-based solid acids is very small, and most of the acidic centers exist on the catalyst surface. Increasing the specific surface area of the catalyst is an important means to increase the number of acidic sites and thus improve the catalytic activity of the acid (Huang LL, Song CC, Liu YC, et al. Enhancement of catalytic esterification by tuning molecular diffusion in sulfonated carbon [J]. Microporous and Mesoporous Materials, 2021, 318: 111024.). Solid acids have been widely used as acid catalysts. Although they are still in the development stage, they still have great potential to be explored. Summary of the invention
[0005] In order to further improve the efficiency of esterification reaction, the invention provides a hydrophobic mesoporous TiO2 / carbonaceous composite material and its preparation method and application, specifically using mesoporous titanium dioxide loaded with sulfonic acid-based carbonaceous material and its application in high-efficiency esterification after modification with aminosilane coupling agent, which meets the needs of industrial production and has great industrial application potential in catalyzing esterification reaction to synthesize lubricating oil.
[0006] The hydrophobic mesoporous TiO2 / carbonaceous composite material of the present invention includes B acid (sulfonic acid) and L acid (titanium dioxide) centers, and the synergistic effect between the two can enhance the catalytic activity. On this basis, the present invention introduces hydrophobic groups and basic amino functional groups through the modification of aminosilane coupling agents, and forms an inner salt structure with the sulfonic acid group, effectively preventing the sulfonic acid group from being lost and leached during the reaction, maintaining the catalytic activity while improving the quality of the product, and realizing acid-base synergistic catalysis. The hydrophobic mesoporous TiO2 / carbonaceous composite material of the present invention has high catalytic activity and stability in esterification reactions.
[0007] In order to achieve the purpose of the present invention, the technical solution adopted is:
[0008] A method for preparing a hydrophobic mesoporous TiO2 / carbonaceous composite material comprises the following steps:
[0009] Prepare a mixed solution of ethanol and distilled water, weigh a certain amount of mesoporous TiO2 loaded with sulfonic acid carbonaceous material (referred to as TiO2 / C-SO3H material) and aminosilane coupling agent, add them to the prepared mixed solution, and react with ultrasonic oscillation (the reaction time is preferably 2±1h). After the reaction, separate the solid product and wash it with anhydrous ethanol, and dry the washed solid product (the drying temperature is preferably 120±10°C), and finally obtain a hydrophobic mesoporous TiO2 / carbonaceous composite material (referred to as TiO2 / C-SO3H / NH2) with acid-base synergistic catalytic performance;
[0010] TiO2 / C-SO3H material is a mesoporous TiO2 material synthesized by a solvent-free self-assembly method using tetrabutyl titanate as a titanium source, and then loaded with carbon dots with sulfonic acid groups under hydrothermal conditions.
[0011] Furthermore, the selection of an aminosilane coupling agent is provided, and the aminosilane coupling agent is selected from any one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.
[0012] Furthermore, the mass ratio of TiO2 / C-SO3H to aminosilane coupling agent is 10:1 to 1:1.
[0013] Furthermore, the preparation of mesoporous TiO2 material includes the following steps:
[0014] Weigh a certain proportion of polyethyleneimine, acetic acid and tetrabutyl titanate, grind them in a mortar for 3 to 6 minutes to form a uniform viscous composite material. Transfer the obtained viscous composite material to a crucible, place it in a muffle furnace for heat treatment for a certain period of time, and obtain highly crystallized mesoporous TiO2.
[0015] The mass ratio of polyethyleneimine to acetic acid is 1:1-1:4, and the mass ratio of polyethyleneimine to tetrabutyl titanate is 1:1-1:5.
[0016] The heating temperature of the muffle furnace is 450-550° C., and the heating time is 3-5 hours.
[0017] Furthermore, the preparation of TiO2 / C-SO3H material includes the following steps: weigh a certain proportion of mesoporous TiO2, furfural and hydroxyethyl sulfonic acid, fully disperse them in distilled water (generally stirred for 0.5 to 1 hour), and then transfer them to a polytetrafluoroethylene-lined high-pressure reactor, put the reactor into an oven and heat it for a certain period of time (the product changes from white to black), wait for the reactor to cool to room temperature, centrifuge the mixture in the reactor, wash and dry it to obtain a composite material, named TiO2 / C-SO3H.
[0018] The molar ratio of the mesoporous TiO2 to furfural is 1:1 to 2:1 (more preferably 1:1 to 1.3:1), and the molar ratio of furfural to hydroxyethyl sulfonic acid is 2:1 to 3:1.
[0019] The invention is based on the fact that furfural can improve the loading rate, and the furfural is removed by in-situ loading on titanium dioxide, the loading rate is not high, and generally the loaded substances will react with Ti-OH.
[0020] The heating temperature of the reactor in the oven is 160-200° C., and the heating time is 3-6 hours.
[0021] The present invention also provides an application of a hydrophobic mesoporous TiO2 / carbonaceous composite material having acid-base synergistic catalytic performance, which is specifically used as a catalyst for esterification reaction.
[0022] Furthermore, the catalytic esterification of trimethylolpropane (TMP) and n-valeric acid comprises the following steps: feeding trimethylolpropane (TMP) and n-valeric acid in a molar ratio of 1:3 to 1:4 into a reaction vessel, and sequentially connecting a thermometer, a condenser, etc.; turning on a magnetic stirrer, raising the temperature until all reactants are dissolved, adding a TiO2 / C-SO3H / NH2 composite material thereto, wherein the mass percentage of the TiO2 / C-SO3H / NH2 composite material catalyst is 1% to 20% of the reactants (trimethylolpropane + n-valeric acid), and then carrying out an esterification reaction at a reaction temperature of 170 to 200°C, and the esterification reaction time is 6 to 8 hours.
[0023] Compared with the prior art, the present application has achieved the following beneficial effects: TiO2 has some open metal sites that can be used as Lewis acid sites, so when the carbon dots carrying sulfonic acid groups are loaded, the unsaturated open sites will be able to combine well with -C-SO3H nanoparticles, and the sulfonic acid groups are used as B acid sites. When the prepared composite catalytic material catalyzes the esterification reaction, B acid and L acid form a synergistic catalytic effect, thereby improving the selectivity of the reaction product and enabling the conversion rate of the raw material to reach 100%. The reaction has the advantages of mild conditions, high reaction yield, and short reaction time, and the catalytic effect of the composite material on the esterification reaction can still reach 88.6% after multiple cycles of catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The powder diffraction characterization results of TiO2 / C-SO3H / NH2 prepared in Example 1;
[0025] Figure 2 This is the STEM-EDS mapping diagram of C element / N element / O element / S element / Ti element of TiO2 / C-SO3H / NH2 prepared in Example 1. DETAILED DESCRIPTION
[0026] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0027] The present invention is further described in detail below in conjunction with embodiments:
[0028] Embodiment 1:
[0029] (1) Weigh 0.45 g of polyethyleneimine, 1 mL of acetic acid and 1.7 g of tetrabutyl titanate and grind them in a mortar for 5 min to form a uniform viscous composite material. The resulting composite material is transferred to a crucible and placed in a muffle furnace for heat treatment at 450 °C for 4 h to form highly crystalline mesoporous TiO2.
[0030] (2) Weigh 2 g of mesoporous TiO2, 1.5 g of furfural and 0.9 g of isethionic acid, add 60 mL of distilled water and stir for 1 h, then transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined autoclave and perform hydrothermal reaction at 180 °C for 4 h. After the reaction, wash the product with distilled water 3 times and anhydrous ethanol 3 times. After the solid product is dried at 80 °C for several hours, a sample is collected and the obtained product is named TiO2 / C-SO3H.
[0031] (3) Prepare a mixed solution of ethanol and distilled water (ethanol: water = 15:85), weigh 0.6 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 and add them to the mixed solution, and ultrasonically vibrate for 2 h. After the reaction, separate the solid product and wash it three times with anhydrous ethanol. Dry the washed solid product at 120 ° C to obtain the modified material and name it TiO2 / C-SO3H / NH2.
[0032] The prepared TiO2 / C-SO3H / NH2 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 99.99% in 6h, and the triester yield reached 93.56% after 7h. The product color was golden yellow.
[0033] Embodiment 2:
[0034] (1) The same as step (1) in Example 1, specifically: 0.45 g of polyethyleneimine, 1 mL of acetic acid and 1.7 g of tetrabutyl titanate were weighed and ground in a mortar for 5 min to form a uniform viscous composite material. The obtained composite material was transferred to a crucible and placed in a muffle furnace for heat treatment at 450° C. for 4 h to form highly crystalline mesoporous TiO2.
[0035] (2) Different from step (2) in Example 1, the mass of mesoporous TiO2 is 1.5 g. Specifically, 1.5 g of mesoporous TiO2, 1.5 g of furfural and 0.9 g of isethionic acid were weighed, mixed, and 60 mL of distilled water was added and stirred for 1 h. The mixed solution was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave and subjected to hydrothermal reaction at 180° C. for 4 h. After the reaction, the product was washed with distilled water 3 times and anhydrous ethanol 3 times. The solid product was dried at 80° C. for several hours and then a sample was collected. The obtained product was named TiO2 / C-SO3H.
[0036] (3) Prepare a mixed solution of ethanol and distilled water (ethanol: water = 15:85), weigh 0.6 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 and add them to the mixed solution, and ultrasonically vibrate for 2 h. After the reaction, separate the solid product and wash it three times with anhydrous ethanol. Dry the washed solid product at 120 ° C to obtain the modified material and name it TiO2 / C-SO3H / NH2.
[0037] The prepared TiO2 / C-SO3H / NH2 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 99.99% in 7h, the triester yield was 90.34% after 7h, and the product color was golden yellow.
[0038] Embodiment 3:
[0039] (1) The same as step (1) in Example 1, specifically: 0.45 g of polyethyleneimine, 1 mL of acetic acid and 1.7 g of tetrabutyl titanate were weighed and ground in a mortar for 5 min to form a uniform viscous composite material. The obtained composite material was transferred to a crucible and placed in a muffle furnace for heat treatment at 450° C. for 4 h to form highly crystalline mesoporous TiO2.
[0040] (2) The difference from step (2) in Example 1 is that the furfural and isethionic acid are reduced year-on-year, and are reduced to 1g and 0.6g, respectively. Specifically: 2g of mesoporous TiO2, 1g of furfural and 0.6g of isethionic acid are weighed, mixed, and 60mL of distilled water is added and stirred for 1h. Then the mixed solution is transferred to a 100mL polytetrafluoroethylene-lined autoclave and hydrothermally reacted at 180°C for 4h. After the reaction, the product is washed with distilled water 3 times and anhydrous ethanol 3 times. The solid product is dried at 80°C for several hours and then a sample is collected. The obtained product is named TiO2 / C-SO3H.
[0041] (3) Prepare a mixed solution of ethanol and distilled water (ethanol: water = 15:85), weigh 0.6 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 and add them to the mixed solution, and ultrasonically vibrate for 2 h. After the reaction, separate the solid product and wash it three times with anhydrous ethanol. Dry the washed solid product at 120 ° C to obtain the modified material and name it TiO2 / C-SO3H / NH2.
[0042] The prepared TiO2 / C-SO3H / NH2 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 90.23% in 8h, and the triester yield reached 75.56% after 7h. The product color was golden yellow.
[0043] Embodiment 4:
[0044] (1) The same as step (1) in Example 2, specifically: 0.45 g of polyethyleneimine, 1 mL of acetic acid and 1.7 g of tetrabutyl titanate were weighed and ground in a mortar for 5 min to form a uniform viscous composite material. The obtained composite material was transferred to a crucible and placed in a muffle furnace for heat treatment at 450° C. for 4 h to form highly crystalline mesoporous TiO2.
[0045] (2) Different from step (2) in Example 2, the mass of mesoporous TiO2 is 1.5g, and the amount of furfural and isethionic acid is proportionally reduced to 1g and 0.6g, respectively. Specifically, 1.5g of mesoporous TiO2, 1g of furfural and 0.6g of isethionic acid are weighed, mixed, and 60mL of distilled water is added and stirred for 1h. The mixed solution is then transferred to a 100mL polytetrafluoroethylene-lined autoclave and hydrothermally reacted at 180°C for 4h. After the reaction, the product is washed with distilled water 3 times and anhydrous ethanol 3 times. The solid product is dried at 80°C for several hours and then a sample is collected. The obtained product is named TiO2 / C-SO3H.
[0046] (3) Prepare a mixed solution of ethanol and distilled water (ethanol: water = 15:85), weigh 0.6 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 and add them to the mixed solution, and ultrasonically vibrate for 2 h. After the reaction, separate the solid product and wash it three times with anhydrous ethanol. Dry the washed solid product at 120 ° C to obtain the modified material and name it TiO2 / C-SO3H / NH2.
[0047] The prepared TiO2 / C-SO3H / NH2 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatograph, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 87.94% in 8h, and the triester yield reached 70.21% after 7h. The product color was golden yellow.
[0048] Embodiment 5:
[0049] (1) The same as step (1) in Example 1, specifically: 0.45 g of polyethyleneimine, 1 mL of acetic acid and 1.7 g of tetrabutyl titanate were weighed and ground in a mortar for 5 min to form a uniform viscous composite material. The obtained composite material was transferred to a crucible and placed in a muffle furnace for heat treatment at 450° C. for 4 h to form highly crystalline mesoporous TiO2.
[0050] (2) The difference from step (1) in Example 1 is that the mass of isethionic acid is 0.7 g. Specifically, 2 g of mesoporous TiO2, 1.5 g of furfural and 0.7 g of isethionic acid were weighed, mixed, and 60 mL of distilled water was added and stirred for 1 h. The mixed solution was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave and subjected to hydrothermal reaction at 180° C. for 4 h. After the reaction, the product was washed with distilled water 3 times and with anhydrous ethanol 3 times. The solid product was dried at 80° C. for several hours and then a sample was collected. The obtained product was named TiO2 / C-SO3H.
[0051] (3) Prepare a mixed solution of ethanol and distilled water (ethanol: water = 15:85), weigh 0.6 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 and add them to the mixed solution, and ultrasonically vibrate for 2 h. After the reaction, separate the solid product and wash it three times with anhydrous ethanol. Dry the washed solid product at 120 ° C to obtain the modified material and name it TiO2 / C-SO3H / NH2.
[0052] The prepared TiO2 / C-SO3H / NH2 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 98.30% in 7h, and the triester yield reached 89.93% after 7h. The product color was golden yellow.
[0053] Embodiment 6:
[0054] The TiO2 / C-SO3H / NH2 catalyst prepared in Example 1 was used in a catalyst recycling experiment for catalyzing the esterification reaction of n-valeric acid and trimethylolpropane.
[0055] (1) Catalyst cycle experiment
[0056] Trimethylolpropane (TMP) and n-valeric acid were added to a 100 mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were installed. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5 g of catalyst TiO2 / C-SO3H / NH2 was added, magnetic stirring was turned on, the reaction started and timing was started, and after 7 hours, the reaction liquid was analyzed by gas chromatography and quantitative nuclear magnetic resonance.
[0057] After the reaction liquid was cooled, the catalyst was centrifuged and washed three times with anhydrous ethanol, and dried in an oven at 80°C to obtain a one-cycle TiO2 / C-SO3H / NH2. The reaction conditions remained unchanged, and the conversion rate of trimethylolpropane was 99.99%, and the triester yield reached 93.56%.
[0058] (2) Catalyst cycle two experiments
[0059] Trimethylolpropane (TMP) and n-pentanoic acid were added to a 100 mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were installed. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, and a cycle of TiO2 / C-SO3H / NH2 was added. The magnetic stirring was turned on, the reaction started and the timing was started. After 7 hours, the reaction liquid was analyzed by gas chromatography and quantitative nuclear magnetic resonance.
[0060] After the reaction liquid was cooled, the catalyst was separated by centrifugation, washed three times with anhydrous ethanol, and dried in an oven at 80°C to obtain a one-cycle TiO2 / C-SO3H / NH2. The reaction conditions remained unchanged, and the conversion rate of trimethylolpropane was 95.60%, and the triester yield reached 91.76%.
[0061] (3) Catalyst cycle three times experiment
[0062] Based on step (2) of this embodiment, the TiO2 / C-SO3H / NH2 of one cycle is modified into TiO2 / C-SO3H / NH2 of two cycles, and other steps and conditions remain unchanged. Accordingly, TiO2 / C-SO3H / NH2 of three cycles is obtained.
[0063] After 7 hours, the reaction solution was analyzed by gas chromatography and quantitative nuclear magnetic resonance, and the conversion rate of trimethylolpropane was 92.80%, and the triester yield was 90.00%.
[0064] (4) Catalyst cycle four times experiment
[0065] Based on step (2) of this embodiment, the TiO2 / C-SO3H / NH2 of one cycle is modified into TiO2 / C-SO3H / NH2 of three cycles, and other steps and conditions remain unchanged. Accordingly, TiO2 / C-SO3H / NH2 of four cycles is obtained.
[0066] After 7 hours, the reaction liquid was analyzed by gas chromatography and quantitative nuclear magnetic resonance, and the conversion rate of trimethylolpropane was 90.30% and the triester yield was 88.76%.
[0067] (5) Catalyst cycle five times experiment
[0068] Based on step (2) of this embodiment, the TiO2 / C-SO3H / NH2 of one cycle is modified into TiO2 / C-SO3H / NH2 of four cycles, and other steps and conditions remain unchanged. Accordingly, TiO2 / C-SO3H / NH2 of five cycles is obtained.
[0069] After 7 hours, the reaction solution was analyzed by gas chromatography and quantitative nuclear magnetic resonance, and the conversion rate of trimethylolpropane was 88.66% and the triester yield was 86.54%.
[0070] Through the analysis of the results of the catalyst recycling experiment on the esterification reaction of valeric acid and trimethylolpropane catalyzed by TiO2 / C-SO3H / NH2, it can be known that TiO2 / C-SO3H / NH2 can still maintain an ultra-high catalytic efficiency after five cycles of catalytic experiments on the esterification reaction of valeric acid and trimethylolpropane. After 5 cycles, the conversion rate of trimethylolpropane can reach 88.66%, and the yield of triester (the product after all three hydroxy groups are esterified) can reach 86.54%.
[0071] Embodiment 7:
[0072] The TiO2 / C-SO3H / NH2 catalyst prepared in Example 1 was used as a catalyst in an experiment to catalyze the esterification reaction of levulinic acid and ethanol.
[0073] Dissolve 1mmol of levulinic acid in 10ml of ethanol, then transfer the mixture to a 100ml Teflon-lined stainless steel autoclave, and add 80mg of catalyst TiO2 / C-SO3H / NH2. The reaction is carried out at 100°C, with a stirring speed of 1000r / min and a reaction time of 4h. After the reaction, the autoclave is quickly cooled with ice water. The solid catalyst is separated by centrifugation, and the product is quantitatively analyzed by gas chromatography. The conversion rate of levulinic acid is 93.62% in 4h, and the product color is golden yellow.
[0074] Embodiment 8:
[0075] The TiO2 / C-SO3H / NH2 catalyst prepared in Example 1 was used as a catalyst in an experiment of catalyzing the esterification reaction of acetic acid and cyclohexanol.
[0076] Add acetic acid and cyclohexanol in a feed ratio of 1:1.6 to a 100mL four-necked flask, and add 10mL cyclohexane as a water-carrying agent. Prepare a thermometer, condenser, etc. Add 0.3g of catalyst TiO2 / C-SO3H / NH2, turn on magnetic stirring, and when the temperature rises to 100℃, the reaction starts and timing is started. Samples are taken every 1h and analyzed by gas chromatograph. The reaction is terminated after the required reaction time is reached. The product is quantitatively analyzed by gas chromatograph, and the conversion rate of acetic acid is 90% at 100℃ for 5h, and the product color is golden yellow.
[0077] Embodiment 9:
[0078] Example 9 Compared with Example 1, the mass ratio of TiO2 / C-SO3H and 3-aminopropyltriethoxysilane KH-550 in step (3) is 4.23:1, 1.2 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 are weighed, and the other operations are the same as steps (1) (2) (3) of Example 1. The obtained product is named TiO2 / C-SO3H-NH2-1.
[0079] The prepared TiO2 / C-SO3H / NH2-1 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2-1 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 99.99% in 6h, the triester yield was 87.21% after 7h, and the product color was golden yellow.
[0080] Embodiment 10:
[0081] Example 10 Compared with Example 1, the mass ratio of TiO2 / C-SO3H and 3-aminopropyltriethoxysilane KH-550 in step (3) is 8:1, 2.4 g of TiO2 / C-SO3H and 0.3 mL of 3-aminopropyltriethoxysilane KH-550 are weighed, and the other operations are the same as steps (1) (2) (3) of Example 1. The obtained product is named TiO2 / C-SO3H-NH2-2.
[0082] The prepared TiO2 / C-SO3H / NH2-1 was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H / NH2-1 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 99.99% in 6h, the triester yield was 89.93% after 7h, and the product color was golden yellow.
[0083] From the test results of Example 9, Example 10 and Example 1, it can be seen that when the dosage ratio of TiO2 / C-SO3H and aminosilane coupling agent is changed, the effect on the conversion rate of the reaction is not very obvious, but the selectivity of the final product trimethylolpropane triester is lower than that of Example 1. The research results show that as the dosage of aminosilane coupling agent increases relatively, the selectivity of trimethylolpropane triester gradually increases.
[0084] Comparative Example 1
[0085] The difference between Comparative Example 1 and Example 1 is that only step (1) is performed, which is exactly the same as step (1) of Example 1.
[0086] Experiment on the esterification reaction of trimethylolpropane and n-pentanoic acid catalyzed by TiO2: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 13.74% in 8h, and the triester yield was 3.5% after 7h.
[0087] Comparative Example 2
[0088] 1.5 g of furfural and 0.9 g of isethionic acid were weighed, mixed, added with 60 mL of distilled water and stirred for 1 h, then the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and subjected to hydrothermal reaction at 180 ° C for 4 h. After the reaction, the product was washed with distilled water 3 times and anhydrous ethanol 3 times. The solid product was dried at 80 ° C for several hours and then the sample was collected. The obtained product was named TiO2-0 / C-SO3H.
[0089] The prepared TiO2-0 / C-SO3H was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2-0 / C-SO3H was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatograph, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 70.36% in 8h, the triester yield was 40.75% after 7h, and the product color was dark brown.
[0090] From the test results of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that the conversion rate of TiO2 used in the esterification reaction is very limited; it is difficult for the sulfonic acid group to form a sufficient number of acid centers alone, the conversion rate is limited and the tri-ester yield is not high; when titanium dioxide is used as the L acid center and sulfonic acid is used as the B acid center, the synergistic effect between the two can enhance the catalytic activity, the number of acid centers gradually reaches saturation, and the conversion rate and ester yield of the reaction are greatly improved. The products obtained by adding amino-modified catalysts are all golden yellow, while the products obtained by using amino-free catalysts are very dark in color, which is caused by the loss of a small amount of sulfonic acid groups into the reaction system, resulting in excessive oxidation.
[0091] Comparative Example 3:
[0092] Comparative Example 3 is different from Example 1 in that only steps (1) and (2) are performed, and the surface modification of the surface ...
[0093] The prepared TiO2 / C-SO3H was used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid were added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. were configured. First, the oil bath temperature was raised to 60°C. When all the raw materials were dissolved and the reaction liquid became clear and transparent, the temperature was raised to 180°C, 0.5g of catalyst TiO2 / C-SO3H was added, magnetic stirring was turned on, the reaction started and timing was started, samples were taken at intervals of 1h and analyzed by gas chromatography, and the reaction was terminated after the required reaction time was reached. The selectivity of the final product was investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane was 99.99% in 7h, the triester yield reached 85% after 7h, and the product was black.
[0094] Comparative Example 4:
[0095] Comparative Example 4 is different from Example 1 in that: Steps (1) (2) (3) are performed. The prepared TiO2 / C-SO3H / NH2 is used to catalyze the esterification reaction of n-pentanoic acid and trimethylolpropane: trimethylolpropane (TMP) and n-pentanoic acid are added to a 100mL four-necked flask at a feed ratio of 1:4, and a thermometer, condenser, etc. are configured. First, the oil bath temperature is increased to 60°C. When all the raw materials are dissolved and the reaction liquid becomes clear and transparent, the temperature is increased to 170°C, 0.5g of catalyst TiO2 / C-SO3H / NH2 is added, magnetic stirring is turned on, the reaction starts and timing is started, samples are taken at intervals of 1h and analyzed by gas chromatograph, and the reaction is terminated after the required reaction time is reached. The selectivity of the final product is investigated by quantitative nuclear magnetic resonance. The conversion rate of trimethylolpropane is 97.90% in 6h, and the triester yield is 87.61% after 7h.
[0096] From the test results of Comparative Example 3 and Example 1, it can be seen that when the system is not modified with aminosilane coupling agent, the effect on the conversion rate of the reaction is not very obvious, but the selectivity of the final product trimethylolpropane triester is significantly lower than that of Example 1. The modification of aminosilane coupling agent not only increases the specific surface area, pore volume and pore size of the material to a certain extent, but also introduces -NH2 groups, further improving the catalytic activity. The product obtained by the catalyst without amino modification has a very dark color, which is caused by the loss of a small amount of sulfonic acid groups into the reaction system, resulting in excessive oxidation.
[0097] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a hydrophobic mesoporous TiO2 / carbonaceous composite material, characterized in that: The steps include: (1) Preparation of mesoporous titanium dioxide by solvent-free self-assembly method; (2) Preparation of TiO2 / C-SO3H composite catalytic materials Weigh a certain amount of mesoporous TiO2, furfural and isethionic acid, mix them, add distilled water and stir, then transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, perform hydrothermal reaction at a certain temperature, wash, filter and dry, and then obtain TiO2 / C-SO3H; the molar ratio of mesoporous TiO2 to furfural is 1:1~2:1, and the molar ratio of furfural to isethionic acid is 2:1~3:1; (3) Preparation of TiO2 / C-SO3H / NH2 materials A mixed solution of ethanol and distilled water was prepared, TiO2 / C-SO3H and aminosilane coupling agent were weighed and added to the prepared mixed solution, ultrasonic oscillation was reacted for a period of time, and after the reaction was completed, the solid product was separated by centrifugation and washed with distilled water and ethanol, and the washed product was dried to finally prepare a modified material named TiO2 / C-SO3H / NH2.
2. The method for preparing the hydrophobic mesoporous TiO2 / carbonaceous composite material according to claim 1, characterized in that: In step (1), mesoporous TiO2 is prepared by a solvent-free self-assembly method, comprising the following steps: weighing a certain proportion of polyethyleneimine, acetic acid and tetrabutyl titanate and stirring them into a light yellow viscous gel, transferring them to a crucible, placing them in a muffle furnace for heat treatment to form highly crystalline mesoporous TiO2; The mass ratio of polyethyleneimine to acetic acid is 1:1-1:4, and the mass ratio of polyethyleneimine to tetrabutyl titanate is 1:1-1:5; The muffle furnace heating temperature is 450-550°C, and the heating time is 3-5h.
3. The method for preparing the hydrophobic mesoporous TiO2 / carbonaceous composite material according to claim 1, characterized in that: The molar ratio of the mesoporous TiO2 to furfural in step (2) is 1:1 to 1.3:
1.
4. The method for preparing the hydrophobic mesoporous TiO2 / carbonaceous composite material according to claim 1, characterized in that: The hydrothermal reaction temperature of step (2) is 160-200°C, and the heating time is 3-6 hours.
5. The method for preparing the hydrophobic mesoporous TiO2 / carbonaceous composite material according to claim 1, characterized in that: The mass ratio of TiO2 / C-SO3H to aminosilane coupling agent is 10:1~1:
1.
6. The method for preparing the hydrophobic mesoporous TiO2 / carbonaceous composite material according to claim 1, characterized in that: The aminosilane coupling agent is selected from any one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane or a mixture of the two.
7. Application of the hydrophobic mesoporous TiO2 / carbonaceous composite material prepared by the preparation method according to claim 1, characterized in that: Used as a catalyst for the esterification of valeric acid and trimethylolpropane.
8. Application of the hydrophobic mesoporous TiO2 / carbonaceous composite material prepared by the preparation method according to claim 1, characterized in that: It is used as a catalyst for the esterification reaction of n-valeric acid and trimethylolpropane. The esterification reaction temperature is 170~200 ºC and the reaction time is 6~8 h. The mass percentage of the TiO2 / C-SO3H / NH2 composite catalyst is 1%~20% of the reactants.
Citation Information
Patent Citations
Preparation method for solid multi-porous catalyst containing Bronsted and Lewis acid
CN106111194A
Phosphotungstic acid- and sulfonic acid-functionalized organosilicon composite material with mesoporous structure and preparation method
CN106669841A